Ductus venosus: From the anatomy to fetal well being evaluation - Duarte, Geraldo; Marcolin, Alessandra Cristina; Crott, Gerson Cláudio; Gonçalves, Carla Vitola; Berezowski, Aderson Tadeu (Medicina (Ribeirao Preto), 2001)
The ductus venosus is a blood vessel unique to the fetal circulation which functions as a shunt between the umbilical vein and inferior vena cava. Well-oxygenated blood from the umbilical vein will course almost directly through the ductus venosus towards the foramen ovale and left heart favoring flow to vital organs as the fetal brain. It becomes functionally impervious to blood just after birth, in the majority of mammals. In obstetrics, Doppler ultrasound scan has largely been used to examine the fetal arterial system. Recently, more attention has been paid to the venous system. Assessment of venous flow velocity waveforms can play an important role in the surveillance of fetal well-being. The ductus venosus velocimetry can be altered in fetal diseases. The most striking feature is the reduced or reversed flow during atrial contraction commonly found in fetuses with congenital heart defects, arrhythmias, twin-twin transfusion syndrome and serious intrauterine growth restriction. This text includes a review of the anatomic and physiologic characteristics of fetal ductus venosus and the importance of its evaluation by prenatal ultrasound.